Synthesis of hierarchical TS-1 zeolite via a novel three-step crystallization method and its excellent catalytic performance in oxidative desulfurization. (15th January 2017) - Du, Qi; Guo, Yiping; Duan, Huanan; Li, Hua; Chen, Yujie; Liu, Hezhou
Graphical abstract: Abstract: Hierarchical TS-1 (HTS-1) zeolite has been successfully synthesized through a novel three-step crystallization method by using a cheap and eco-friendly polymer PVA as the mesopore template. The HTS-1 particles possess an interesting stacking structure and are constructed of smaller crystals with an average diameter of 30 nm. The mesopores of HTS-1 are formed by the stacking of the smaller TS-1 nanocrystals. The catalytic results show that the HTS-1 exhibits much higher catalytic activity than conventional TS-1 in the oxidative desulfurization of dibenzothiophene (DBT) and 4, 6-dimethyldibenzothiophene (4, 6-DMDBT) due to the presence of intracrystal mesopores. In addition, the three-step crystallization method plays a key role in the preparation of HTS-1, which effectively solves the problem that PVA is unstable and unsuitable to be used as mesopore template under high crystallization temperature.